2004
DOI: 10.1037/0033-2909.130.5.711
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Universal Positivity Bias in Attributions? A Meta-Analytic Review of Individual, Developmental, and Cultural Differences in the Self-Serving Attributional Bias.

Abstract: Researchers have suggested the presence of a self-serving attributional bias, with people making more internal, stable, and global attributions for positive events than for negative events. This study examined the magnitude, ubiquity, and adaptiveness of this bias. The authors conducted a meta-analysis of 266 studies, yielding 503 independent effect sizes. The average d was 0.96, indicating a large bias. The bias was present in nearly all samples. There were significant age differences, with children and older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

76
771
6
36

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,079 publications
(889 citation statements)
references
References 327 publications
76
771
6
36
Order By: Relevance
“…It appears that victimization is a trauma that works itself "under the skin" by either altering the physiological response to stress (Ouellet-Morin et al 2011), by gene-environment interaction whereby victimized children who later develop depression symptoms differ in genotype (Benjet et al 2010;Sugden et al 2010) and finally, repeated experience of victimization may equip an individual with a range of cognitive biases characteristic of depression (Mezulis et al 2004). There is evidence for all three routes in the development of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that victimization is a trauma that works itself "under the skin" by either altering the physiological response to stress (Ouellet-Morin et al 2011), by gene-environment interaction whereby victimized children who later develop depression symptoms differ in genotype (Benjet et al 2010;Sugden et al 2010) and finally, repeated experience of victimization may equip an individual with a range of cognitive biases characteristic of depression (Mezulis et al 2004). There is evidence for all three routes in the development of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, victimized children who later develop clinically significant symptoms show systematic differences in the expression of depression-linked genes (e.g.5-HTTLPR) compared to those who remain symptom-free or exhibit only transient symptoms (Sugden et al 2010). Finally, repeated experience of victimization may equip an individual with a range of cognitive biases rendering him/her susceptible to the self-defeating ideations characteristic of depression (Mezulis et al 2004). Victims (Woods et al 2009) and those exhibiting symptoms of depression (Beck 2008;Evans et al 2005) have been shown to have numerous biases in cognitive processing, e.g., deeper encoding of negative information in memory or interpretation of ambiguous material as negative (Dearing and Gotlib 2009;Hertel and Brozovich 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Con la finalidad de poder continuar estudiando la re lación de los individuos con la nor ma, se plan tea como desafío para futuras investigaciones, el desarrollo de instrumentos que ate núen la deseabilidad social en la eva luación de este tema, ya que en general en las escalas que evalúan aspectos donde se establece una auto-presentación, existe cierta estabilidad en las respuestas, en este caso de re chazo a la transgresión, lo que estaría afectando a los indicadores de consistencia interna de la escala utilizada (Mezulis, Abramson, Hyde & Hankin, 2004).…”
Section: Investigacionesunclassified
“…La escala total tuvo una consistencia interna de 0,69 en el presente estudio. Es importante mencionar que para el desarrollo del estudio se tomaron en cuenta puntuaciones con coeficientes alfa de Cronbach de nivel moderado y alto (α > 0,50), según el criterio de Cohen (Mezulis, Abramson, Hyde & Hankin, 2004). En el caso de obtener niveles menores de consistencia interna, se observaron resultados en estudios con las mismas escalas y se vio la pertinencia de incluir estos en el análisis y discusión de los resultados, atendiendo también a la postura de Mezulis et al (2004), quienes plantean que escalas que apelan a la autopresentación tienden a presentar cierta tendencia estable a maximizar los atributos positivos y minimizar los negativos.…”
Section: Instrumentosunclassified
“…Es importante mencionar que para el desarrollo del estudio se tomaron en cuenta puntuaciones con coeficientes alfa de Cronbach de nivel moderado y alto (α > 0,50), según el criterio de Cohen (Mezulis, Abramson, Hyde & Hankin, 2004). En el caso de obtener niveles menores de consistencia interna, se observaron resultados en estudios con las mismas escalas y se vio la pertinencia de incluir estos en el análisis y discusión de los resultados, atendiendo también a la postura de Mezulis et al (2004), quienes plantean que escalas que apelan a la autopresentación tienden a presentar cierta tendencia estable a maximizar los atributos positivos y minimizar los negativos. Debido a lo anterior, se optó por no considerar los resultados relacionados con la dimensión Relaciones positivas con otros y mantener los de las dimensiones Autonomía y Propósito en la vida, que, aunque obtuvieron coeficientes menores a 0,5, presentaron esta misma tendencia en otros estudios revisados (Arellano, 2011;Balbuena, 2013).…”
Section: Instrumentosunclassified